2008
DOI: 10.1515/epoly.2008.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of iota-carrageenan gels prepared with various CaCl2 content: A fluorescence study

Abstract: Iota carrageenan gels prepared with various CaCl 2 content were completely dried and then swelled in water vapor. Steady-state fluorescence (SSF) technique was used to monitor the swelling process of each iota carrageenan gels at various temperatures. Pyranine was used as a fluorescence probe. Apparent fluorescence intensity, I increased as swelling time increased for all gel samples. The increase in I was modelled using Li-Tanaka equation from which the swelling time constants, τ 1 and cooperative diffusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Gels prepared from hydroxyalkyl j-carrageenan derivatives demonstrated decreased syneresis and could contribute to a wider industrial use of these polysaccharides. Recently, Tari and Pekcan (2008) demonstrated that the association of j-carrageenan with CaCl 2 can change the swelling properties of carrageenan gels, emphasizing the commercial relevance of carrageenans chemical modifications.…”
Section: Chemical Modificationsmentioning
confidence: 99%
“…Gels prepared from hydroxyalkyl j-carrageenan derivatives demonstrated decreased syneresis and could contribute to a wider industrial use of these polysaccharides. Recently, Tari and Pekcan (2008) demonstrated that the association of j-carrageenan with CaCl 2 can change the swelling properties of carrageenan gels, emphasizing the commercial relevance of carrageenans chemical modifications.…”
Section: Chemical Modificationsmentioning
confidence: 99%
“…Κ-carrageenan containing hydroxyalkyl groups has already been developed to create a gel with a decreased syneresis and therefore, a broader industrial scope [182]. The association of κ-carrageenan with CaCl2 changes the swelling capacity of the gel [183]. Another often used derivatization type characteristic for these polysaccharides is alkalization.…”
Section: Natural Saps Based On Carrageenan and Its Derivativesmentioning
confidence: 99%